Desenvolvimento de uma forma farmacêutica de liberação modificada baseado no delineamento de experimentos (DOE) - Felizardo Junior, Carlos Alberto (Universidade Federal de São Carlos, 2025)
One of the biggest challenges in the process of developing and registering a drug is to develop a formulation that is equivalent in terms of comparative dissolution in relation to the reference drug marketed, meeting the corresponding requirements described in legislation through the design around approach. Through the study of chemometrics, using factorial planning and statistical tools, it is possible to develop a solid pharmaceutical form that meets the recommended equivalence and dissolution profile criteria. Contraception is a practice widely used by women all over the world, and oral contraceptives are among the most widely used classes. They have several advantages over other classes of contraceptives, however, in some situations, they can pose certain risks to patients. The development of isolated progestins has proven to be effective and favourable for addressing issues related to some patient risks. National legislation establishes the need to prove the equivalence and bioequivalence of a drug in relation to its reference, in which its efficacy and safety have been proven. To this end, it is important to evaluate the impact of bioavailability through in vitro studies such as dissolution profile tests, through several collections of the dissolution medium at appropriate times, evaluating the percentage of dissolved drug. The presented work aims to develop a solid pharmaceutical form of prolonged release using multivariate experimental factorial design tools. By applying factorial design as a chemometric tool, we can design and optimize a formulation by identifying critical quality parameters, mainly reducing the number of necessary tests without compromising the quality of the information and reliability of the results
Development of a modified release drug form based on the Design of experiments (DOE)
Keywords: Design around; Planejamento fatorial; Delineamento de experimentos; Quimiometria; Design of experiments; Desenvolvimento de formulação; Liberação modificada; OUTROS::QUIMICA INDUSTRIAL